Screening of wild type Streptomyces isolates able to overproduce clavulanic acid - Marques, Daniela A. Viana; Santos-Ebinuma, Valéria de Carvalho [UNESP]; Oliveira, Patrícia Maria Sobral de; Lima, Gláucia Manoella de Souza; Araújo, Janete M.; Lima-Filho, José L.; Converti, Attilio; Pessoa-Júnior, Adalberto; Porto, Ana L. F. (Sociedade Brasileira de Microbiologia, 2014)
The selection of new microorganisms able to produce antimicrobial compounds is hoped for to reduce their production costs and the side effects caused by synthetic drugs. Clavulanic acid is a β-lactam antibiotic produced by submerged culture, which is widely used in medicine as a powerful inhibitor of β-lactamases, enzymes produced by bacteria resistant to antibiotics such penicillin and cephalosporin. The purpose of this work was to select the best clavulanic acid producer among strains of Streptomyces belonging to the Microorganism Collection of the Department of Antibiotics of the Federal University of Pernambuco (DAUFPE). Initially, the strains were studied for their capacity to inhibit the action of β-lactamases produced by Klebsiella aerogenes ATCC 15380. From these results, five strains were selected to investigate the batch kinetics of growth and clavulanic acid production in submerged culture carried out in flasks. The results were compared with the ones obtained by Streptomyces clavuligerus ATCC 27064 selected as a control strain. The best clavulanic acid producer was Streptomyces DAUFPE 3060, molecularly identified as Streptomyces variabilis, which increased the clavulanic acid production by 28% compared to the control strain. This work contributes to the enlargement of knowledge on new Streptomyces wild strains able to produce clavulanic acid by submerged culture.
Keywords: clavulanic acid; beta-lactamases inhibitor; Streptomyces screening; submerged culture; growth kinetics